Comparison of Cultureset to a Conventional Tissue Culture—Fluorescent-Antibody Technique for Isolation and Identification of Herpes Simplex Virus - Fayram, Sandra L. (1983)
The isolation and identification of herpes simplex virus types 1 and 2 from clinical specimens with a 48-h system was compared with a conventional tissue culture detection method.